2015
DOI: 10.3390/ijerph121214959
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of the Copper, Zinc, and Cadmium Absorption Capacities of Aquatic Plants in Heavy Metal-Polluted Water

Abstract: The use of aquatic plants for phytoremediation is an important method for restoring polluted ecosystems. We sought to analyze the capacity of different aquatic plant species to absorb heavy metals and to summarize available relevant scientific data on this topic. We present a meta-analysis of Cu, Zn, and Cd absorption capacities of aquatic plants to provide a scientific basis for the selection of aquatic plants suitable for remediation of heavy-metal pollution. Plants from the Gramineae, Pontederiaceae, Cerato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(47 citation statements)
references
References 59 publications
5
40
1
1
Order By: Relevance
“…The correlations between the uptakes of the various metals were mostly strong, indicating that plants that successfully removed one studied metal likely also removed the others (Table 4), corroborating Li et al (2015), who found correlations of r ¼ 0.74-0.90 between the uptakes of Cd, Cu, and Zn in a large range of species. In fact, the correlations between the uptakes of different metals in our study were often stronger than the correlations between metal uptake and the other measured traits, indicating that there are traits not included in this study that could further explain the variation between species.…”
Section: Relationship Between Uptake Patterns Of Metalssupporting
confidence: 82%
See 2 more Smart Citations
“…The correlations between the uptakes of the various metals were mostly strong, indicating that plants that successfully removed one studied metal likely also removed the others (Table 4), corroborating Li et al (2015), who found correlations of r ¼ 0.74-0.90 between the uptakes of Cd, Cu, and Zn in a large range of species. In fact, the correlations between the uptakes of different metals in our study were often stronger than the correlations between metal uptake and the other measured traits, indicating that there are traits not included in this study that could further explain the variation between species.…”
Section: Relationship Between Uptake Patterns Of Metalssupporting
confidence: 82%
“…Plants with large fibrous root systems removed markedly more metals than did plants with coarser roots (Table 2). Larger root systems have greater surface areas, which absorb and adsorb more metals (Li et al 2015); this is especially important for Pb, which readily binds to organic matter such as roots (Ignatius et al 2014). The lack of restricting tissue, such as exodermis, in young fine roots enables high absorption to the apoplast.…”
Section: Influence Of Roots and Belowground Partsmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil heavy metal pollution mainly refers to the deposition of heavy metals, such as mercury, cadmium, lead, chromium, and other bio-toxic significant heavy elements in the soil [1], resulting in concentrations that exceed background values. Metals are not biodegradable, and through biological amplification, their concentrations can be increased thousands of times, with significant effects on human health [2]. In recent years, discharges of large volumes of heavy metals from industrial activity and mining, with final deposition in the soil, have led to increases in soil heavy metal concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…За двох гранично допустимих концентрацій у комбікормі Мідь нагромаджується у всіх тканинах організму коропів однаково, а Цинк -більшою мірою у зябрах і печінці, ніж у скелетних м'язах. За Ключевые слова: ФЕРМЕНТЫ, ПРОДУКТЫ ПЕРЕКИСНОГО ОКИСЛЕНИЯ ЛИПИДОВ, МЕДЬ, ЦИНК, ЖАБРЫ, ПЕЧЕНЬ, СКЕЛЕТНЫЕ МЫШЦЫ, КАРПЫ As a result of industrial and agricultural production, fishponds can accumulate increased concentrations of heavy metals [1,2], those, depending on their properties, valence and content, can affect metabolic processes in the freshwater fishes [3][4][5], mainly as a constituents of numerous enzymes [6]. For instance, Zinc is a part of the antioxidant enzyme superoxide dismutase; also, it regulates the activity of Δ 3 -, Δ 4 -, Δ 5 -and Δ 6 -desaturases [6][7][8].…”
unclassified